Effect of Audio Assisted Relaxation Therapy on Level of Blood Pressure among Mothers with Pregnancy Induced Hypertension - Shasi Bala1 , Lekha Viswanath2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: The incidence of PIH is about 8-10% of pregnancies. Hypertensive disorder of pregnancy if unchecked will result in eclampsia with generalized convulsions, HELLP syndrome etc. It is usually managed with medicines. There are various non-pharmacological treatment like muscle relaxation, meditation, breathing etc. which are used to control of hypertension. Present study was aimed to assess the effectiveness of audio assisted relaxation therapy on level of blood pressure among mother with pregnancy induced hypertension. Method: Experimental approach with one group pretest- posttest design was used for the study. Study was conducted among 30 antenatal mothers diagnosed with PIH admitted in Kamla Nehru Hospital, Shimla H.P, selected by using convenience sampling technique. Semi structured interview schedule is used to collect background information and sphygmomanometer was used to measure the level of blood pressure. The blood pressure (BP) was monitored three times a day for two days to obtain a baseline data and average of it was considered as pre-test. Audio assisted relaxation therapy was then administered for 20 minutes per sessions, two times a day for three days. The blood pressure (BP) was monitored before and after each session of relaxation therapy Results: The mean posttest systolic is BP, 139.81 mm of Hg was significantly lower than the mean pretest systolic BP, 146.45 mm of Hg. The mean posttest diastolic BP, 87.63 mm of Hg was also lower than the mean pretest diastolic BP, 92.06 mm. Both differences were significant at the level of <0.001. Discussion: The result of present study shows there is a significant difference in BP before and after intervention. So audio assisted relaxation therapy can be used as an effective add on intervention for the management of with women hypertension during pregnancy.